Application of Administrative Sanctions in Decisions on State Administrative Cases at the State Administrative Court - Terbit Fajar; Arif Wibowo (JUSTICES: Journal of Law, 2023)
In carrying out its duties and authority, it is felt that the State Administrative Court (PTUN) in Indonesia has not met the expectations of the people seeking justice. This journal discusses the application of administrative sanctions, the obstacles they face and the concept of effective application of administrative sanctions in TUN case decisions at the Semarang PTUN. The research method is socio legal. The results of the research are first, the application of administrative sanctions in TUN case decisions at the Semarang PTUN is not optimal. Second, the obstacles are low awareness of TUN Officials, lack of active participation from the Defendant and lack of supervision, there are no regulations regarding a special budget. Third, the concept of effective implementation is that there is a legal basis for the PTUN to include administrative sanctions in its decision, revise the provisions of the relevant articles, there needs to be a clear commitment from the TUN Agency or Officials and their superiors, the need for supervision.